Fluid Learning Centrum PUCP - Sotomayor, Manuel (2021)
For over one hundred years, Pontificia Universidad Católica del Perú (PUCP) has been committed to promoting high academic performance and to educating individuals who contribute to the development of Peruvian society. As its business school, Centrum PUCP is based on the fundamental ideals of academic rigour, diverse scientific and humanistic approaches, ethical principles, Catholic values, discrepancy culture, and tolerance, as part of a global context characterised by constant change, demands, and needs that require agile and flexible adaptation. Therefore, the aim of PUCP is to educate students in good business practices, contributing towards building a better world. With this purpose in mind, our mission is to transform individuals into agents of change who have a positive impact on society. Our vision is to continue to be recognised as the leading business school in Peru, ranked in the top 10 of Latin America. To achieve this, we educate conscious leaders who focus on the common good and who are critical thinkers and behave responsibly in accordance with the ethical principles and values of the business field and all other environments in which they interact, both inside and outside the country. As a result, based on the educational model of Pontificia Universidad Católica del Perú (PUCP), Centrum PUCP has designed a Learning Management Model that not only reflects our definition of learning, but also how we design and manage our educational proposal. It serves as a guide to integrate and implement our competency-based model within the curriculum and methodology, as well as apply it to our assessment and learning certifications. This is why we have developed Fluid Learning Centrum PUCP, our learning management model. In the following section we will explore its foundations and structure, assess its advantages, and examine the characteristics that provide added value to our school and its community.